ANALISIS PERAN STAKEHOLDER DALAM PENGEMBANGAN DESA WISATA “EKOWISATA TAMBAKSARI” KECAMATAN WANAREJA KABUPATEN CILACAP - Maya Wijayanti, Dwi; Djumiarti, Titik; Hayu Dwimawanti, Ida (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The tourism sector has the potential to improve the quality of life for communities through increased tourism activities in Indonesia, both nationally and globally. Based on Provincial Regulation No. 2 of 2019 for Central Java, this regulation governs the development of tourist villages; however, in its implementation, several issues have been found indicating the suboptimal role of stakeholders in the